The information age combat model: a vision for a discrete event simulation approach. (2017) - Khasawneh, Mahmoud T.; Shearer, Nevan; Rabadi, Ghaith; Bowling, Shannon
Network centric operations (NCO) has been dubbed the most significant revolution in military affairs (RMA) in the past 200 years. The promise of NCO is based on the notion that information sharing and connectivity is fundamental to the effectiveness of a combat force. This is due to the ability of a properly networked force to self-synchronise itself as it engages enemy forces. The information age combat model (IACM) is a popular representation of NCO. Previous research at modelling the IACM has so far focused solely at using agent-based modelling. That work produced significant contributions to the IACM literature. However, it has proven to be computationally expensive. IACM simulations must be sustainable as research into IACM evolves and more NCO complexities are introduced. This research will propose a discrete-event simulation (DES) approach to model the IACM. The paper will present the basis upon which DES was selected for this purpose and will illustrate how the DES approach can provide significant improvements in terms of the time and computational power needed to run IACM simulations.